Humanitarian assistance and resilience-building: Impact of Fadama III-AF II on food security and livelihood restoration in Northeastern Nigeria - Nkonya, Ephraim M.; Bawa, Dauda; Kato, Edward; Maurice, David; Murtala, Nasiru; Nuhu, Hadiza; Kwaghe, Patrick; Bila, Yakubu; Sani, Rabiu (International Food Policy Research Institute, 2019)
The ongoing insurgency in northeastern Nigeria has led to the loss of over 20,000 lives and about 4,500 abductions since 2002 and, in 2015 alone, caused an economic loss of about US$450 million, equivalent to 5.7 percent of northeastern Nigeria’s gross domestic product.1 As of October 2018, there were 2.03 million internally displaced people (IDPs) and 1.64 million returnees a total of 3.7 million people in need of humanitarian support, or 14 percent of northeastern Nigeria’s population.2 Communities affected by conflict experience severe food and nutrition deprivation and difficult mental health conditions.3 Beyond political and military efforts aimed at ending conflicts, approaches to helping conflict-affected communities have evolved over time from a focus on humanitarian support to more dynamic and sustainable strategies. These approaches follow provision of humanitarian assistance with support for restoring livelihoods and building resilience against potential shocks.4 This new approach of humanitarian assistance plus resilience-building has experienced both successes and challenges. The challenges have largely stemmed from the limited experience of actors, short intervention periods, and insufficient resources to address the many problems experienced by conflict-affected communities. In collaboration with 65 development partners, the government of Nigeria through its Presidential Committee on the North East Initiative (PCNI) has implemented strategies both to restore peace and security and to provide humanitarian support and restore livelihoods for IDPs, returnees, and other conflict-affected people. The most recent of these is the Fadama III–AF II project, a US$50 million investment that combines humanitarian assistance with resilience-building. To evaluate the impact of this project, IFPRI conducted a study to assess its impacts on food and nutrition security and restoration of livelihoods.